2016
DOI: 10.1039/c6ra17775a
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular enzyme engineering in complex nanometer-thin biomimetic organosilica layers

Abstract: Enzyme shielding at the surface of silica nanoparticles was performed using different mixtures of biomimetic building blocks. The performances of the nanobiocatalysts are strongly impacted by the chemical composition of the shielding layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In order to produce the samples called EH 3 -T/A [1/1] , EH 3 -T/A [4/1] , EH 3 -T/A [6/1] , EH 3 -T/A [10/1] , EH 3 -TBz/A [4/1] , EH 3 -TUr/A [4/1] , EH 3 -TBu/A [4/1] , EH 3 -THm/A [4/1] , and EH 3 -TBzUrBuHm/A [4/1] , the EH 3 (100 μg mL –1 ) was immobilized according to the procedure described above. Consequently, the shielding was performed following the method previously published . TEOS and all the other silanes were added to the reaction mixture according to the quantities reported in Table S2 and allowed to react under moderate stirring (1 h, 20 °C, 400 g ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to produce the samples called EH 3 -T/A [1/1] , EH 3 -T/A [4/1] , EH 3 -T/A [6/1] , EH 3 -T/A [10/1] , EH 3 -TBz/A [4/1] , EH 3 -TUr/A [4/1] , EH 3 -TBu/A [4/1] , EH 3 -THm/A [4/1] , and EH 3 -TBzUrBuHm/A [4/1] , the EH 3 (100 μg mL –1 ) was immobilized according to the procedure described above. Consequently, the shielding was performed following the method previously published . TEOS and all the other silanes were added to the reaction mixture according to the quantities reported in Table S2 and allowed to react under moderate stirring (1 h, 20 °C, 400 g ).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the shielding was performed following the method previously published. 19 TEOS and all the other silanes were added to the reaction mixture according to the quantities reported in Table S2 and allowed to react under moderate stirring (1 h, 20 °C, 400g). Subsequently, APTES (0.090 mmol) was added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different mixtures of OSs building blocks sharing chemical similarities with natural amino acids were used. [13] In more detail: the hydroxyl group of hydroxymethyl-triethoxysilane mimics polar amino acids (e.g. serine, threonine); propyl-triethoxysilane and benzyltriethoxysilane serve as aliphatic and aromatic building blocks mimicking leucine and phenylalanine, respectively.…”
Section: Nanomaterials For Biocatalysismentioning
confidence: 99%
“…15 We have previously introduced a synthetic chemical strategy to fully shield immobilised enzymes in an organosilica layer at the surface of silica particles (SPs). 16,17 We demonstrated that this organosilica layer protects the enzyme in a so environment enhancing enzyme stability while maintaining catalytic activity. However, fully shielded enzymes can only convert small substrates, which can diffuse through the protective layer.…”
Section: Introductionmentioning
confidence: 96%